(untitled) (Filologia e Linguística Portuguesa, 1999)
With this paper I intend to contribute to the study of collective denomination in European Portuguese. However it can not be considered an exhaustive work on this subject. As I consider the structure of words fundamental to understand their meaning and use, I’ll pay special attention to this aspect of collective nouns. Firstly, I’ll expose, although briefly, the concept of “collective noun”, specially as it is presented at Cunha & Cintra (1984). Then the different types of morphological structures of nouns presenting a collective meaning will be described. Finally, I’ll list the suffixes involved in the construction of Portuguese collective denominal nouns.